Melatonin: Unveiling the functions and implications in ocular health - Ji Zhang; Haixiang Zhou; Yuting Cai; Shigeo Yoshida; Yun Li; Yedi Zhou (Elsevier, 2024)
Melatonin, a versatile hormone produced by the pineal gland, has garnered considerable scientific interest due to its diverse functions. In the eye, melatonin regulates a variety of key processes like inhibiting angiogenesis by reducing vascular endothelial growth factor levels and protecting the blood-retinal barrier (BRB) integrity by enhancing tight junction proteins and pericyte coverage. Melatonin also maintains cell health by modulating autophagy via the Sirt1/mTOR pathways, reduces inflammation, promotes antioxidant enzyme activity, and regulates intraocular pressure fluctuations. Additionally, melatonin protects retinal ganglion cells by modulating aging and inflammatory pathways. Understanding melatonin's multifaceted functions in ocular health could expand the knowledge of ocular pathogenesis, and shed new light on therapeutic approaches in ocular diseases. In this review, we summarize the current evidence of ocular functions and therapeutic potential of melatonin and describe its roles in angiogenesis, BRB integrity maintenance, and modulation of various eye diseases, which leads to a conclusion that melatonin holds promising treatment potential for a wide range of ocular health conditions.